Effect of the load-bearing characteristics of the cushions on the longitudinal dynamics of the electric trains and the high-cycle fatigue of coupling - V. I. Belyaev (Вестник Научно-исследовательского института железнодорожного транспорта, 2023)
Introduction. Measurements of forces in couplings on electric trains of different categories and types (including different types of drawbars) showed that the level of forces in couplings on suburban electric trains is higher than on urban express trains, despite the lower number of starts and stops and the presence of buffers on suburban electric trains to absorb some of the longitudinal forces. In addition, a higher frequency (statistical probability) of occurrence of these forces was observed in suburban electric trains, which determines a higher load on automatic couplers in suburban electric trains with an automatic coupler installed in accordance with GOST 3475-81 than in ES2G city electric trains, where the cushions are combined with the coupling body. The main objective of the study was to determine the load on the couplers of electric trains of different categories and types, as well as to determine the parameters of the cushions of the couplers that have the greatest influence on their load.Materials and methods. The research methods include experimental measurement of longitudinal forces in inter-car couplings of electric trains under operating conditions with statistical processing of the results, and analysis of the effect of cushions indicators on the longitudinal dynamics of the train.Results. The authors analyse the effect of the initial tightening force on the changes in the level of acting forces and the loading of drawbars during electric train operation. The most significant effect of this force is found to be on the longitudinal dynamics of the train and on the load on the couplings.Discussion and conclusion. Reducing the initial tightening force has a positive effect on the longitudinal dynamics of railcars, according to the results of tests measuring the force levels in couplings. The results obtained would form the basis for further research under varying conditions and for conducting train tests.